Geographical variation of floral scents in generalist entomophilous species with variable pollinator communities. (21st December 2021) - de Manincor, Natasha; Andreu, Benjamin; Buatois, Bruno; Lou Chao, Hineiti; Hautekèete, Nina; Massol, François; Piquot, Yves; Schatz, Bertrand; Schmitt, Eric; Dufay, Mathilde
Abstract: Floral scents are considered major attractants for pollinator species and scent composition is likely to be under pollinator‐mediated selection. Relatively, few studies have investigated geographical variation in floral scents in plant species with generalist pollination, and little is known about the mechanism behind this variation, often interpreted as the result of local adaptation to pollinators without considering phenotypic plasticity. One possible way to investigate this question is to compare floral bouquets both in natural populations and in populations reared under controlled conditions. We compared the identity and proportions of volatile organic compounds (VOCs), collected on plants both in the field and in the greenhouse, emitted by four generalist plant species found in six calcareous grasslands distributed along an environmental and diversity gradient. We recorded pollinator visits in the field to document geographical variation of pollinator communities associated with each plant species. We then analysed the relation between VOCs and pollinator variation using a redundancy analysis (RDA). We found that VOC composition differed among species and among populations, but also between field and greenhouse. The RDA showed a significant effect of the variation in pollinator communities associated with the variation in the VOCs emission, even after removing potential confounding effects, suggesting some stability in the compounds attractive to a given pollinator species. However, only one species showed significant geographical differences among populations tested in both conditions, suggesting local genetic adaptation. Another species showed geographical variation in VOC proportion in the field, but these results were not confirmed by the greenhouse extractions, suggesting an effect of phenotypic plasticity. Our findings suggest that geographical variation of floral scent may, in some cases, be genetically based and possibly explained by pollinator‐mediated selection, even in generalist pollinated species, which represent the large majority of pollination systems. However, our results also showed significant phenotypic plasticity, suggesting that studies of floral volatiles must be conducted in natural populations to obtain a representative picture of the signal that can be potentially perceived by pollinators. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Résumé: Les odeurs florales sont considérées comme des composants attractifs majeurs pour les pollinisateurs et la composition des odeurs est devrait être soumise à une sélection médiée par les pollinisateurs. Relativement peu d'études se sont focalisées sur la variation géographique des odeurs florales chez les espèces végétales à pollinisation généraliste, et peu de choses sont connues sur les causes de cette variation, souvent interprétée comme le résultat d'une adaptation locale aux pollinisateurs, sans tenir compte de l'effet de la plasticité phénotypique. Une façon d'étudier cette question est de comparer les bouquets floraux à la fois dans les populations naturelles et dans les populations cultivées en conditions contrôlées. Nous avons comparé l'identité et les proportions des composés organiques volatils (COV), prélevés sur les plantes à la fois sur le terrain et en serre, au sein de quatre espèces végétales généralistes présentes dans six prairies calcaires réparties le long d'un gradient environnemental et de diversité. Nous avons mesuré les visites des pollinisateurs sur le terrain afin de documenter la variation géographique des communautés de pollinisateurs associées à chaque espèce de plante. Nous avons ensuite analysé la relation entre les COV et la variation des pollinisateurs en utilisant une analyse de redondance (RDA). Nous avons constaté que la composition des COV différait entre espèces et entre populations, mais aussi entre le terrain et la serre. La RDA a montré un effet significatif de la variation des communautés de pollinisateurs associée à la variation de l'émission des COV, même après avoir éliminé les effets confondants potentiels, suggérant une certaine stabilité dans les composés attractifs pour une espèce de pollinisateur donnée. Cependant, une seule espèce a montré des différences géographiques significatives entre les populations testées dans les deux conditions, ce qui suggère une adaptation génétique locale. Une autre espèce présente une variation géographique dans la proportion de COV sur le terrain, mais ces résultats n'ont pas été confirmés par les extractions en serre, ce qui suggère un effet de plasticité phénotypique. Nos résultats suggèrent que la variation géographique de l'odeur florale peut, dans certains cas, avoir une base génétique et peut‐être expliquée par la sélection médiée par les pollinisateurs, même chez les espèces avec une pollinisation généralistes, qui représentent la grande majorité des systèmes de pollinisation. Cependant, nos résultats ont également montré un rôle significatif de la plasticité phénotypique, suggérant que les études sur les bouquets floraux doivent être menées dans des populations naturelles pour obtenir une image représentative du signal potentiellement perçu par les pollinisateurs.